A Review of Maize Seed Production Technology in Spring-Sown Area - Liu, Qinzhi; Huang, Yiyun; Gao, Zicheng; Yu, Haiyan (Scientific Journal of Technology, 2025)
In recent years, with the rapid development of modern agriculture in China and the continuous acceleration of maize industrialization, the planting area of maize in spring sowing area is constantly improving, and the area of seed production is also expanding. However, while the area of spring sowing corn seed production continues to expand, the phenomenon of unqualified seed quality, yield reduction and even no harvest caused by improper seed production technology and cultivation management occurs from time to time, which is bound to bring serious economic losses to seed production units and seed farmers. In view of this problem, this paper summarizes the effective measures of maize seed production in the spring sowing area, and points out the key links, in order to break through the bottleneck in maize single seed production, and finally achieve the goal of win-win situation for seed production units and seed farmers.